Pengaruh campur kode dalam bahasa iklan televisi edisi 2023: Analisis dan implikasinya - Rahmayani, Rizka Dwi; R., Syahrul; Amir, Amril; Basri, Irfani (Universitas Lampung, 2024)
Indonesia boasts diversity in its ethnicities, nationalities, and languages. In the context of a bilingual society, the exclusive use of a single language in communication becomes impractical. Hence, the phenomenon of code-switching commonly occurs, which involves the mixing of two or more languages during language interaction. This study focuses on analyzing code-switching in television advertising language in the year 2023. The aim of this research is to identify various forms of code-switching utilized in television advertising language, including phrases, clauses, hybrids, and word repetitions. The research methodology employed is qualitative, utilizing data collection techniques such as advanced listening, recording, coding, and transcription. Data analysis is conducted using the distributional method. The results of this study indicate that modern television advertisements often combine various language elements to achieve a more effective communication impact with the audience.Keywords: code, mixing, advertise, television